2006
DOI: 10.1039/b517937h
|View full text |Cite
|
Sign up to set email alerts
|

Highly enantioselective addition of ketones to nitroolefins catalyzed by new thiourea–amine bifunctional organocatalysts

Abstract: A new and effective organocatalytic system: primary amine derived chiral thiourea catalyst and AcOH-H2O additive, which converts different ketones to gamma-nitroketones in high yields (82-99%) and enantioselectivities (90-99%) has been described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(68 citation statements)
references
References 50 publications
4
61
0
3
Order By: Relevance
“…Moreover, some of these catalysts have some important features to emphasize such as bipyrrolidine 2, which is a very active organocatalyst for the anticonjugate addition of α-hydroxyketones to nitrostyrenes. [8] A similar sense of relative stereoinduction has been shown by chiral primary amine-thiourea catalysts 13 [19] and 17 [23] developed by Tsogoeva and Jacobsen, respectively, in the conjugate addition of acyclic ketones to nitroolefins giving predominantly the anti Michael adducts due to the participation of a Z-enamine intermediate. Catalysts 4, [10b] 16, [22] 19, [25] and 20 [26] are very effective systems to perform the Michael addition under aqueous conditions such as brine (catalyst 4) or neat water.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Moreover, some of these catalysts have some important features to emphasize such as bipyrrolidine 2, which is a very active organocatalyst for the anticonjugate addition of α-hydroxyketones to nitrostyrenes. [8] A similar sense of relative stereoinduction has been shown by chiral primary amine-thiourea catalysts 13 [19] and 17 [23] developed by Tsogoeva and Jacobsen, respectively, in the conjugate addition of acyclic ketones to nitroolefins giving predominantly the anti Michael adducts due to the participation of a Z-enamine intermediate. Catalysts 4, [10b] 16, [22] 19, [25] and 20 [26] are very effective systems to perform the Michael addition under aqueous conditions such as brine (catalyst 4) or neat water.…”
Section: Introductionmentioning
confidence: 73%
“…Furthermore, catalyst 15 and the fluorous sulfonamide 19 can be easily recycled by precipitation and fluorous solid-phase extraction, respectively, and reused without significant loss of activity and stereoselectivity. [7] up to 76% ee 2 [8] up to 81% ee 3 [9] up to 99% ee [18] up to 86% ee 13 [19] up to 91% ee [25] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…同年, 作者对硫脲 32 的结构进行修饰改造, 设计合 成了新的硫脲 33 (Scheme 14). 将硫脲 33 用于催化酮与 芳香硝基烯烃的不对称加成反应, 能以高产率(82%~ 99%)和高立体选择性(顺∶反>83∶17, 90%~99% ee) 得到相应加成产物 [56,58] . 研究还发现, 如果在相同的条 件下, 选用甲基乙基酮等非对称酮与硝基苯乙烯反应, 则会得到相反的非对映选择性结果(顺∶反=14∶86), 对映选择性也相当高(>99%).…”
Section: Methodsunclassified
“…[4][5][6] In particular, bifunctional amine-thiourea-based catalysts have proved to be efficient in various asymmetric transformations owing to the ability of the thiourea moiety to highly activate carbonyl or nitro groups through double hydrogenbonding interactions. 7,8 Therefore, this kind of organocatalyst has been widely studied in [12][13][14][15][16][17][18][19][20][21][22] Since Tsogoeva 23 and Jacobsen 24 demonstrated that a primary amine-thiourea catalyst can act as efficient bifunctional catalyst for the asymmetric nitro Michael addition, such bifunctional organocatalysts have attracted much attention owing to their easy preparation from chiral diamines. [25][26][27][28][29][30][31][32] However, the chiral scaffold of these reported organocatalysts is limited and is mostly derived from 1,2-diaminocyclohexane and 1,2-phenylethylenediamine.…”
Section: Introductionmentioning
confidence: 99%